Application of Mendelian randomized research method in oncology research: bibliometric analysis - Jiahao Chen; Yunli Wang; Rongsheng Jiang; Yawei Qu; Yan Li; Yang Zhang (Frontiers in Oncology)
BackgroundCancer has always been a difficult problem in the medical field, and with the gradual deepening of Genome-wide association studies (GWAS), Mendelian randomization methods have been increasingly used to study cancer pathogenesis. In this study, we examine the literature on Mendelian cancer, summarize the status of the research, and analyze the development trends in the field.MethodsPublications on “Mendelian Randomization - Cancer” were retrieved and downloaded from the Web of Science Core Collection database. CiteSpace 6.2.R4, VOSviewer 1.6.19, Scimago Graphica 1.0.38, Bibliometrix R-package, and a bibliometric online analysis platform were used for data analysis and visualization. An in-depth analysis of country or region, authors, journals, keywords, and references was performed to provide insights into the content related to the field.ResultsA total of 836 articles were included in the analysis; 643 authors from 72 countries had published articles related to the field. China and Harvard University (among countries and institutions, respectively) had the highest number of articles. Martin, Richard M and Smith, George Davey were the largest contributors. A total of 27 cancers have been studied, with breast, colorectal, and liver cancers being the most studied.ConclusionThis study is the first to use bibliometric methods to visualize the application of Mendelian randomization analysis in the field of cancer, revealing research trends and research frontiers in the field. This information will provide a strong reference for cancer researchers and epidemiologic researchers.